Генетичний алгоритм з жадібним стохастичним оператором схрещування для передбачення третинної структури білка - Гуляницький, Л.Ф.; Чорножук, С.А. (Кібернетика та комп’ютерні технології, 2020)
Розроблено новий генетичний алгоритм, особливістю якого є запропонований жадібний стохастичний оператор схрещування. Застосування пропонованого алгоритму досліджується на задачі передбачення третинної структури білка. Наведено результати обчислювального експерименту. Цель работы. Описание генетического алгоритма с новым жадным стохастическим оператором скрещивания. В сравнении предлагаемого алгоритма с лучшими известными имплементациями генетических и миметических алгоритмов, используемых для определения пространственной структуры белка. Результат. Работа предлагаемого алгоритма сравнивается с другими на базе 10 известных цепей длиной 48, для которых найден глобальный минимум свободной энергии, впервые предложенных в [13]. Алгоритм нашел 9 из 10 пространственных структур, на которых достигается глобальный минимум свободной энергии, а также продемонстрировал лучшее среднее значение решений, чем алгоритмы, с которыми он сравнивался. The purpose of the article is to describe a genetic algorithm with a new greedy stochastic crossover operator, reveal its advantages and disadvantages, compare the proposed algorithm with the best-known implementations of genetic and memetic algorithms for the spatial protein structure prediction, and make conclusions with future steps suggestion afterward. Result. The work of the proposed algorithm is compared with others on the basis of 10 known chains with a length of 48 first proposed in [13]. For each of the chain, a global minimum of free energy was already pre-calculated. The algorithm found 9 out of 10 spatial structures on which a global minimum of free energy is achieved and also demonstrated a better average value of solutions than the comparing algorithms.